The Accumulation of Heavy Metals in Hydrostemma Motleyi Hook. f. Mabberlay and Hydrilla verticillata Casp. - Lee, C. K; Low, K. S.; Tan, S. H. (1984)
The uptake of heavy metals (copper, zinc, nickel, cadmium and chromium) by Hydrostemma motleyi (Hook.f') Mobberlay and Hydrilla Verticillata Gasp. was studied. The uptake generally increased with increasing metal concentrations. The enrichment factor which relates the metal content in plants to the metal content in cultivation media generally decreased with increasing metal concentrations. Antagonistic action was observed when Hydrostemma motleyi was cultivated in mixed solutions of copper, zinc and nickel. For Hydrilla verticillata, synergistic effect was observed at low concentration of the mixed solution, but at higher concentrations, the effect was reversed. Metal accumulation appears to be species specific. Hydrilla verticillata exhibited a higher tolerance and accumulation capacity for heavy metals than Hydrostemma motleyi. It has the potential of being an indicator species for metal pollution in water.